A comparative study of dietary fiber content, In vitro starch digestibility and cooking quality characteristics of pigmented and non–pigmented traditional and improved rice (Oryza sativa L.). (July 2022) - Rebeira, S.P.; Prasantha, B.D.R.; Jayatilake, D.V.; Dunuwila, G.R.; Piyasiri, C.H.; Herath, H.M.K.W.P.
Graphical abstract: Highlights: Dietary fiber (DF) content is higher in pigmented rice than non-pigmented rice. Pigmented rice has lower starch digestibility than non-pigmented rice. Pigmented rice has lower expected glycemic index values than non-pigmented rice. Climatic variations of rice cultivation do not affect the DF content of rice. There is no difference between the DF content of traditional and improved rice. Abstract: Thirty-two traditional and newly improved pigmented and non-pigmented rice varieties were evaluated for their eating and cooking quality and dietary fiber (DF) content. Seasonal variability of DF content, in–vitro starch digestion rate (DR) and expected glycemic index (eGI) were evaluated using selected representative samples. Rice varieties were categorized either high or intermediate amylose content but with hard, medium or soft gel consistency. Average insoluble dietary fiber (IDF) and soluble dietary fiber (SDF) content ranged between 1.13–6.76% and 0.03–1.00%, respectively. Pigmented rice reported significantly higher IDF content compared to non–pigmented rice and also showed a significant statistical correlation (r > 0.56, P < 0.01) between IDF and pigmentation. There was no seasonal variation observed in rice DF content between two cropping seasons. Pigmented rice varieties showed significantly lower (P < 0.05) starch digestibility and glycemic index values (DR:58.8–66.5; eGI:71.9–76.2) than non–pigmented rice (DR:69.1–71.5; eGI:77.6–79.0). Pigmented rice showed significantly higher negative correlation (r > -0.68, P < 0.01) with DR.